Omega-3 Supplementation in Athletes: Impact on Performance, Recovery After Physical Exercise and Effects on Injury Recovery - Systematic Review - Sadowska, Aleksandra; Śliwa-Tytko, Patrycja; Welkier, Aleksandra; Miśkiewicz, Joanna; Dudek, Aleksandra; Pietrusińska, Patrycja; Moder, Jakub; Sobiński, Adam; Dziewierz, Anna; Kwaśniewska, Paula (Quality in Sport, 2026)
Introduction. The process of recovering from strenuous physical activity is a concern for various groups, ranging from elite athletes to recreationally active individuals. High-force or unfamiliar eccentric exercise routines can cause significant damage to muscle fibers, often leading to soreness, inflammation, and a temporary decline in performance. Given these challenges, there is a growing interest in nutritional strategies, including omega-3 supplementation, to mitigate the adverse effects of intense training and facilitate faster recovery. Purpose of the work. The aim of this article was to conduct a systematic review, characterize the effects of supplementation, and explore the practical benefits of omega-3 supplementation for athletes in terms of muscle performance, recovery, and brain and cardiovascular health. This review synthesizes findings from recent studies to provide insights into the benefits, impact on performance, recovery, effects on injury recovery and potential limitations of omega-3 supplementation for athletes. Materials and methods. A systematic search was conducted in PubMed, Scopus, and Web of Science for articles published between January 2010 and December 2024. Keywords included "omega-3 supplementation," "athletic performance," "sports recovery," and "injury recovery." Eligible studies included randomized controlled trials (RCTs), observational studies, and meta-analyses that focused on omega-3 supplementation in healthy athletes. Results. Several studies have examined the potential ergogenic effects of omega-3 fatty acids. Key findings include endurance, muscle strength and power, reaction time, and cognitive function. Importantly, the evidence consistently supports the role of omega-3 fatty acids in recovery from injury, especially in reducing inflammation. Most studies used doses of 2 to 4 grams of EPA and DHA combined daily. Benefits were typically seen after 4 to 12 weeks of ongoing supplementation.